Low-oxygen storage modulates fruit flavor formation: Metabolic and regulatory insights - Qin Li; Xiaojing Li; Demei Zhang; Jingxin Chen; Yonghong Ge; Penta Pristijono; Hongbo Mi (Food Chemistry, 2026)

LncRNA CCAT1/miR-490-3p/VDAC1 Axis Promotes Colorectal Cancer Progression by Activating Glycolysis - Yongli Ge; Qi Liu; Lijuan Zhao; Wenjuan Mi; Xiaoyan Qi (Biochemical Genetics, 2026)

Long-term observations uncover sustained carbon dioxide emissions from lakes following aquaculture retreat - Jiayu Zhao; Mi Zhang; Wei Xiao; Pei Ge; Juhua Luo; Minliang Jiang; Cheng Hu; Delin Li; Tianyu Zhang; Hongtao Duan; Qitao Xiao; Xuhui Lee (Water Research, 2026)

Extraction of Phyllanthus emblica L. flavonoids by ultrasound-assisted enzymatic hydrolysis method and antioxidant stress effects - Xianghong Xiong; Shengcheng Mi; Xiaojie Xu; Dan Ge; Wu Yan; Qi Lu; Minghua Zhu; Yihong Bao (Natural Product Research, 2026)

Insights into land deformation processes in the Yellow River Delta (China) from synthetic aperture radar interferometry time series and machine learning - Pengfei Ge; Mi Chen; Roberto Tomás; Hui Liu; Kailun Fan; Xi Cheng; Xingyuan Fu; Shuang Wang (Advances in Space Research, 2026)

Trade and port-based resilience analysis under the expansion of the belt and road trade agreement: an integrated economic and environmental assessment - Jackson Jinhong Mi; Shaowei Rui; Hongguang Zhu; Jinfeng Ge; Xinqiang Chen (Frontiers in Marine Science, 2026)
Trade cooperation represents a fundamental and crucial element within the framework of the Belt and Road Initiative. This paper selects representative countries with Belt and Road trade agreement that are under negotiation, under study, and accessible. Employing the Global Trade Analysis Project (GTAP) model, the study simulates seven distinct scenarios for the expansion of these trade agreements, analyzes the economic benefits under different scenarios, and constructs a multi-region input–output table. A Global Trade Analysis Project-Multi Region Input Output (GTAP-MRIO) model is extended to capture carbon flows from maritime trade and port-related logistics sectors. We obtain several findings. Regarding economic benefits, the expansion of the Belt and Road trade agreement can improve China’s terms of trade, increase the scale of China’s total output and total imports, increase GDP growth, and increase social welfare. Regarding industrial output, the output of technology-intensive industries is likely to increase, and the output of energy-intensive industries is predicted to increase significantly. The transfer of carbon emissions from China to other countries is predicted to decrease, and the transfer of carbon emissions from China’s exports comes mainly from energy-intensive industries. These predictions based on model analysis offer theoretical guidance and policy recommendations for the pursuit of green and high-quality sustainable development within the framework of the Belt and Road Initiative.

Suppression of ethylene-responsive MdERF74/75 under low-oxygen storage disrupts aroma formation in apple fruit via fatty acid metabolism pathways - Kaichen Li; Demei Zhang; Qin Li; Jingxin Chen; Yonghong Ge; Jingyi Lv; Jianrong Li; Hongbo Mi (Postharvest Biology and Technology, 2026)

The AMPK-FOXO signaling regulates the transcriptional response of 4EBP to pesticide stress in Tribolium castaneum - Daojie Guan; Zhichao Wang; Changpeng Liu; Huichen Ge; Mi Zhou; Shu Fang; Kun Qian; Jianjun Wang (Pesticide Biochemistry and Physiology, 2026)

Highly oxidized germacrane-type sesquiterpenoid dimers from Elephantopus tomentosus L.: Structural characterization, DFT calculation and anti-hepatoma potential - Zi-Hao Ge; Si-Hui Mi; Wen-Long Kou; Guo-Dong Yao; Bin Lin; Jian Wang; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Causal Links Between the Plasma Lipidome and Cognitive Performance: Targets, Pathways, and Lifestyle Influences - Ran Miao; Qian Wang; Si-liang Ge; Ming Chen; Feng Zhao; Wei-dong Mi; Jiang-bei Cao (Molecular Neurobiology, 2026)

Evolution of China's shipping policies and attention: Evidence from LDA analysis - Yicheng Wang; Jackson Jinhong Mi; Chongqing Chen; Jinfeng Ge; Yanhui Chen (Ocean & Coastal Management, 2025)

An eco-friendly and effective method for isolating essential oil from fresh Kaempferia galanga L.: Process optimization based on entropy weight method and response surface methodology - Qingfen Zhang; Dan Ge; Shengcheng Mi; Qi Lu (Sustainable Chemistry and Pharmacy, 2025)

Dynamic and high methane emission flux in pond and lake aquaculture - Jiayu Zhao; Mi Zhang; Yini Pu; Lei Jia; Wei Xiao; Zhen Zhang; Pei Ge; Jie Shi; Qitao Xiao; Xuhui Lee (Journal of Hydrology, 2025)

Static Stress Triggering Effect on the Surrounding Major Faults and Aftershocks of the 2024 M 7.4 Earthquake in Hualien, Taiwan - Shu-Zhong Sheng; Zi-Fei Mi; Xiao-Juan Zhang; Kun-Peng Ge (Applied Geophysics, 2025)

High-precision Q modeling and Q migration technology and its applications in loess plateau regions - Wei Xu; Hong-Xing Liu; Hong-Gang Mi; Bing Zhang; Jun-Chao Guo; Yong Ge; Jun You (Applied Geophysics, 2024)

A Bibliometric Analysis of Green Shipping: Research Progress and Challenges for Sustainable Maritime Transport - Jackson Jinhong Mi; Yicheng Wang; Nan Zhang; Congzhi Zhang; Jinfeng Ge (Journal of Marine Science and Engineering, 2024)
This paper aims to systematically review and analyze the literature on green shipping, focusing on research trends, key areas, and future directions. A bibliometric analysis is conducted on 1339 articles published between 2000 and 2023, using data from the SCI-EXPANDED and SSCI core collections on the Web of Science platform. Co-occurrence analyses are performed for authors, countries, institutions, and keywords. The analysis reveals exponential growth in green shipping research over the past decade, with a significant increase since 2019. China leads in publication output and international collaboration. Key research areas identified include sustainable development, green energy, green ports, and green supply chain management. Green shipping research is rapidly expanding, emphasizing sustainable practices and technological advancements. Future research is expected to integrate artificial intelligence, big data analytics, and other advanced technologies to further promote sustainability. Strengthening international cooperation and interdisciplinary integration will be crucial for advancing the global green shipping agenda.

Integrated analysis of miRNAome and transcriptome reveals that microgravity induces the alterations of critical functional gene modules via the regulation of miRNAs in short-term space-flown C. elegans - Xinye He; Lei Zhao; Baohang Huang; Ge Zhang; Ye Lu; Dong Mi; Yeqing Sun (Life Sciences in Space Research, 2024)

Aerosol interference with open-path eddy covariance measurement in a lake environment - Lei Jia; Mi Zhang; Wei Xiao; Yini Pu; Zhen Zhang; Hengxin Bao; Pei Ge; Jie Shi; Yang He; Fuyu Yang; Kelly Aho; Peter Raymond; et al. (Agricultural and Forest Meteorology, 2024)

Freeze polymerization to modulate transverse-longitudinal polypyrrole growth on robust cellulose composite fibers for multi-scenario signal monitoring - Zhiying Gao; Chuang Wang; Yanjuan Dong; Juming Yao; Qingling Mi; Dan Ge; Lu Yang; Hou-Yong Yu (Chemical Engineering Journal, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Blockage of ATPase-mediated energy supply inducing metabolic disturbances in algal cells under silver nanoparticles stress - Ruohua Qu; Mi Chen; Jingfu Liu; Qiting Xie; Na Liu; Fei Ge (Journal of Environmental Sciences, 2023)

The role of exosomes and their enhancement strategies in the treatment of osteoarthritis - Linzhen Huang; Ge Dong; Jie Peng; Ting Li; Mi Zou; Kaibo Hu; Yuan Shu; Tao Cheng; Liang Hao (Human Cell, 2023)

Ferulic acid enhanced resistance against blue mold of Malus domestica by regulating reactive oxygen species and phenylpropanoid metabolism - Mi Guo; Canying Li; Rui Huang; Linhong Qu; Jiaxin Liu; Chenyang Zhang; Yonghong Ge (Postharvest Biology and Technology, 2023)

Microgravity alters the expressions of DNA repair genes and their regulatory miRNAs in space-flown Caenorhabditis elegans - Lei Zhao; Ge Zhang; Aiping Tang; Baohang Huang; Dong Mi (Life Sciences in Space Research, 2023)

Porous carbon nanofibers supported Zn@MnO sorbents with high dispersion and loading content for hot coal gas desulfurization - Yu Feng; Man Zhang; Yangjie Sun; Chunyan Cao; Jiancheng Wang; Mingzheng Ge; Weilong Cai; Jie Mi; Yuekun Lai (Chemical Engineering Journal, 2023)

Effects of Selenoprotein S Knockdown on Endoplasmic Reticulum Stress in ATDC5 Cells and Gene Expression Profiles in Hypertrophic Chondrocytes - Hui Wang; Zhengzheng Li; Yinan Liu; Meng Zhang; Yawen Shi; Ying Zhang; Ge Mi; Mengying Wang; Ying He; Yonghui Chen; Chen Chen; Jinghong Chen (Biological Trace Element Research, 2023)

Pre-crosslinking with putrescine improves mechanical and thermal properties of alginate film - Yanqin Zhong; Mingliang Yang; Jingxin Chen; Hongbo Mi; Yonghong Ge; Jingyi Lv; Jianrong Li (Journal of Food Engineering, 2023)

A novel sulfated mannan-carboxymethyl-5-fluorouracil-folic acid conjugates for targeted anticancer drug delivery - Nan Ma; Mi-Hye Kwon; Subramanian Palanisamy; Yunfei Ge; Yutong Zhang; Fang Kou; Lee Dae-Hee; Dong-Jin Lee; Il-Shik Shin; SangGuan You (Carbohydrate Polymers, 2023)

Spatiotemporal variation of cultivated land ecosystem stability in typical regions of Lower Liaohe Plain China based on stress - buffer - response - Hongjun Sui; Ge Song; Wanying Liu; Yuxin Zhang; Ruiqing Su; Quanxi Wang; Gaofeng Ren; Yuqi Mi (Science of The Total Environment, 2023)

Catalytic fast pyrolysis of herbal medicine wastes over zeolite catalyst for aromatic hydrocarbons production - Sicheng Zhou; Shouhang Tang; Ge Li; Shanzhi Xin; Fang Huang; Xiaoye Liu; Tie Mi; Kai Huang; Lixi Zeng (Fuel, 2023)

Pathological Networks Involving Dysmorphic Neurons in Type II Focal Cortical Dysplasia - Yijie Shao; Qianqian Ge; Jiachao Yang; Mi Wang; Yu Zhou; Jin-Xin Guo; Mengyue Zhu; Jiachen Shi; Yiqi Hu; Li Shen; Zhong Chen; Xiao-Ming Li; et al. (Neuroscience Bulletin, 2022)

Effects of different 2A peptides on transgene expression mediated by tricistronic vectors in transfected CHO cells - Yan-mei Li; Meng Wang; Tian-yun Wang; Yong-ge Wei; Xiao Guo; Chun-liu Mi; Chun-peng Zhao; Xiang-xiang Cao; Yuan-yuan Dou (Molecular Biology Reports, 2020)

Identification of a novel strain, Streptomyces blastmyceticus JZB130180, and evaluation of its biocontrol efficacy against Monilinia fructicola - Mi Ni; Qiong Wu; Hong-li Wang; Wei-cheng Liu; Bin Hu; Dian-peng Zhang; Juan Zhao; De-wen Liu; Cai-ge Lu (Journal of Zhejiang University-SCIENCE B, 2019)

Omics for understanding the mechanisms of Streptomyces lydicus A01 promoting the growth of tomato seedlings - Qiong Wu; Mi Ni; Wei-Cheng Liu; Jian-Hong Ren; Ying-Hong Rao; Jie Chen; Cai-Ge Lu (Plant and Soil, 2018)

Molecular characterization and identification of facilitative glucose transporter 2 (GLUT2) and its expression and of the related glycometabolism enzymes in response to different starch levels in blunt snout bream (Megalobrama amblycephala) - Hualiang Liang; Ahmed Mokrani; Hopeson Chisomo-Kasiya; Ogwok-Manas Wilson-Arop; Haifeng Mi; Ke Ji; Xianping Ge; Mingchun Ren (Fish Physiology and Biochemistry, 2018)

Fluorescence Detection of p-Nitrophenol in Water Using Bovine Serum Albumin Capped ag Nanoclusters - Mi Mao; Chun Deng; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2017)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Phylogenetic and functional alpha and beta diversity in temperate and tropical tree communities - Nathan G. Swenson; David L. Erickson; Xiangcheng Mi; Norman A. Bourg; Jimena Forero-Montaña; Xuejun Ge; Robert Howe; Jeffrey K. Lake; Xiaojuan Liu; Keping Ma; Nancai Pei; Jill Thompson; et al. (Ecology, 2012)
The study of biodiversity has tended to focus primarily on relatively information‐poor measures of species diversity. Recently, many studies of local diversity (alpha diversity) have begun to use measures of functional and phylogenetic alpha diversity. Investigations into the phylogenetic and functional dissimilarity (beta diversity) of communities have been far less numerous, but these dissimilarity measures have the potential to infer the mechanisms underlying community assembly and dynamics. Here, we relate levels of phylogenetic and functional alpha diversity to levels of phylogenetic and functional beta diversity to infer the mechanism or mechanisms responsible for the assembly of tree communities in six forests located in tropical and temperate latitudes. The results show that abiotic filtering plays a role in structuring local assemblages and governing spatial turnover in community composition and that phylogenetic measures of alpha and beta diversity are not strong predictors of functional alpha and beta diversity in the forests studied.

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Conjugates of folic acids with BSA-coated quantum dots for cancer cell targeting and imaging by single-photon and two-photon excitation - He Meng; Ji-Yao Chen; Lan Mi; Pei-Nan Wang; Mei-Ying Ge; Yang Yue; Ning Dai (JBIC Journal of Biological Inorganic Chemistry, 2011)